FLOW INJECTION ANALYSIS PHOTOMETRIC DETERMINATION OF IRON (III), USING NEW HOME MADE MICRO PHOTOMETER - شاكر عصام; البدري شروق (Iraqi Journal of Science, 2024)
New micro photometer was constructed in our Laboratory which deals withdetermination of Iron (III) as A red Blood thiocyanate charge transfer complex. Inwhich it was complied well with FIA. Linearity of 97.5% for the range 1-10 ppmand 96.4% for 0.1-1 ppm. The repeatability of result was better than 0.78%. L.O.Dof 0.01 ppm was obtained.The microphotometer was compared well with A.A. resultand with conventional spectrophotometer method.